Land tenure and farming practices: The case of Tiyo Woreda, Arsi, Ethiopia - Gavian, S.; Teklu, A. (Agricultural Economics Society of Ethiopia, 1996)
This paper evaluates the potential problems in the context of mixed crop-livestock system of the Ethiopian highlands. Survey data from the Arsi region are used to describe the prevalence and nature of landlessness. The impact of the current land situation on selected parameters of crop agriculture, field management and interhousehold equity is analyzed. The first part discusses household characteristics. It describes demographic and economic characteristics of household by tenure class. The second part examins access to land with particular reference to types of contracts for croplands and nature of land contracts (security and rights). The third part deals with crop production in relation to input use, crop yields and crop profitability. Land management is the last topic. It disscusses farming problems, land improvement practices, and tree planting.